The Importance of Change Management in Digital Transformation: A Case Study of Schneider Electric’s Global Supply Chain Finance Division (aSSIST Business Review, 2026)
This study analyzes the digital transformation case of Schneider Electric’s Global Supply Chain Finance division to identify the impact of digitalization on management accounting, and to propose strategic recommendations for successful digital transformation through the identification of problems and solutions. Schneider Electric, a multinational corporation headquartered in Paris, France, has pursued digital transformation in management accounting since 2016, implementing various projects aimed at standardizing and centralizing financial and accounting data. The study reveals that insufficient change management—including inadequate employee training and communication, misaligned organizational structures, and unclear role definitions—led to inefficiencies, resistance, and project delays. Based on established change management models including Lewin’s Change Management Model, ADKAR, and Kotter’s 8-Steps, this study provides actionable recommendations to strengthen organizational readiness, improve cross-functional communication, and enhance employee capability-building for successful digital transformation.
Keywords: Digital Transformation; Change Management; Management Accounting; Schneider Electric; ERP